Productivity improvement using industrial engineering tools - How, Sheng Boon (2010)
The aim of this study is to study the implementation of industrial engineering tools in selected manufacturing company to identify the highest defects occurred at the company production lines and propose new methods to the selected manufacturing company for defects reduction and thus improve the productivity of the company. The chosen company is NamHwa Paper Industries (M) SDN. BHD. and the product being analyzed is 1040mm paper. The study mainly focuses on 7 Quality Control. In order to achieve the objective of the study, firstly, the flow of process to produce 1040mm paper was observed. From the observation, there are total of 8 workstations at the company. The workstations are Slitter, Print, Slotter, Glue, Stitching, Partition, Die Cut and Tie workstation. Then, each frequency of defects at the workstation was collected by using check sheets. The data was then arranged according to the highest to lowest frequency in cumulative table and Pareto chart was build base on the cumulative table. Defect with the highest frequency can be identified and was chosen to be analyzed. The workstation chosen for analyzed was Glue workstation. Initially, the original methods imply at glue workstation has very much defects and did not achieve the targeted output. Hence, brainstorming needs to be done to build the cause and effect diagram as detailed as possible causes in each of the broad areas where the causes will be 4M which is Methods, Machines, Manpower and Materials. Based on the cause and effect diagram, solutions were generated. There are few suggestions that can suite the company and improve the productivity of NamHwa Paper Industries (M) SDN. BHD. The solutions are divided the glue paper box into few group before stacking up, use electric fan or airy place for glue workstation, and use table lamp or hair dryer. Cost reduction for each solution was calculated and the solution with highest cost reduction is chosen to increase the productivity of the company.